PENGARUH DUKUNGAN DAN KEADILAN ORGANISASI TERHADAP OCB MELALUI KEPUASAN KERJA - Asril; Kusuma; Efendi Rahmanto; Leny Susilawati A (Program Studi Manajemen, 2025)
This study aims to analyze the effect of perceived organizational support and organizational justice on Organizational Citizenship Behavior (OCB) through job satisfaction as a mediating variable among State Civil Apparatus at the Department of Food Crops, Horticulture and Livestock of East Kutai Regency. This research used a quantitative approach with a survey method. The population consisted of 170 employees, while 135 valid questionnaires were analyzed. Data were processed using Partial Least Square (PLS). The results showed that perceived organizational support had a positive and significant effect on job satisfaction and OCB. Organizational justice also had a positive and significant effect on job satisfaction and OCB. Job satisfaction had a positive and significant effect on OCB. Furthermore, job satisfaction partially mediated the relationship between perceived organizational support and OCB, as well as the relationship between organizational justice and OCB. The findings indicate that increasing organizational support, fair treatment, and employee satisfaction are important strategies to improve extra-role behavior and organizational effectiveness.